Generasi Muda Kok Takut Bersuara? - Hesti Lestari; Masduki Asbari; Deftia Eka Pratiwi; Erfani Fankhiyatun Munawaroh (Journal of Information Systems and Management (JISMA), 2024)
The aim of this study is to encourage young people to no longer be afraid and hesitant to express their opinions.  In this study report, descriptive qualitative methods are used took notes because the data source was obtained by listening to the oral narrative from Mata Najwa's YouTube channel entitled "Today, Young People Are Afraid to Speak Up?  – Young Voices (Part 1)” where the event was hosted by Najwa Shihab as host and attended by several invited guest stars from various circles and representatives from a number of communities.  The results of this study explain the extent of the role and voice of young people.  On October 28, 1928, young Indonesian people from various backgrounds pledged unity to build a nation.  And today, 93 years later, how far has the role and voice of young people gone?  This research began with young people's reduced interest in expressing their opinions to the public.  This is caused by various things such as feelings of fear and lack of support from the community and government.